Peran Pesantren Dalam Mewujudkan Indonesia Emas 2045 Melalui Pendidikan Karakter - Imam Hanafi; Moh. Wardi; Eko Adi Sumitro (Jurnal Ilmiah Edukatif, 2023)
This research examines the role of pesantren (Islamic boarding schools) in realizing a golden Indonesia for 2045. This is significant because pesantren is one of the oldest educational institutions in Indonesia with their variety and characteristics; moreover, it has produced a lot of graduates who have participated in developing Indonesia. This research applied a qualitative library method. The data utilized in this research were secondary data obtained from several journal articles and other library sources that were considered relevant to it. The obtained data were analyzed by using a descriptive analysis. Its results suggest that to realize a golden Indonesia 2045, we should focus on not only how to develop intellectual and intelligent generation but also how to build characters and morals with the principles of independence, service, nationality; these three principles have been implemented in the pesantren.